Meniscal biomechanical alterations in an ACLT rabbit model of early osteoarthritis. Issue 7 (July 2015) - Levillain, A.; Boulocher, C.; Kaderli, S.; Viguier, E.; Hannouche, D.; Hoc, T.; Magoariec, H.
Summary: Objective: The purpose of this study was to analyze the early biomechanical alterations of menisci during the early stage of osteoarthritis (OA) development and to correlate them with the chemical composition and matrix alteration. A particular focus was paid to pathological changes in glycosaminoglycan (GAG) content and collagen fiber architecture. Design: Menisci ( n = 24) were removed from rabbits' knee joints 6 weeks following surgical anterior cruciate ligament transection (ACLT). Both the anterior and posterior regions of medial and lateral menisci were characterized using indentation tests, Raman microspectroscopy (RM), biphotonic confocal microscopy (BCM) and histology. Results: Mechanical and matrix alterations occurred in both regions of medial and lateral menisci. A significant decrease in the mechanical properties was observed in OA menisci, with a mean reduced modulus from 2.3 to 1.1 MPa. Microstructural observations revealed less organized and less compact collagen bundles in operated menisci than in contralateral menisci, as well as a loss of fiber tension. GAG content was increased in OA menisci, especially in the damaged areas. Neither changes in the secondary structure of collagen nor mineralization were detected through RM at this stage of OA. Conclusion: ACLT led to a disorganization of the collagen framework at the early stage of OA development, which decreases the mechanical resistance of the menisci. GAG content increases in response to this degradation. All of these results demonstrate the strong correlation between matrix and mechanical alterations.